Multiphase shear thickening fluid and preparation method thereof

By introducing zeolite imidazole skeleton ZIF-8 as the second dispersed phase particle in the shear thickening liquid, using mechanical stirring and ultrasonic dispersion technology, the problem of dispersed phase particles in the traditional shear thickening liquid was solved, and the shearing was improved The performance of cutting thickening and dispersion stability has achieved the performance adjustment and application value of shear thickening liquid.

CN119220221APending Publication Date: 2024-12-31QINGDAO ZHONGLIAN MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411345276.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The dispersed phase particles in traditional shear thickening liquids are prone to settle, resulting in loss of shear thickening performance and are difficult to adjust, affecting application value.

Method used

Using a multiphase shear thickening fluid system, the zeolite imidazole ester skeleton ZIF-8 is introduced as the second dispersed phase particle. Through mechanical stirring and ultrasonic dispersion technology, the frictional contact and interaction between particles are improved, and the dispersion stability and shearing are enhanced. Thickening properties.

Benefits of technology

The uniform distribution and stability of dispersed phase particles is achieved, the shear thickening performance is improved, the application life of the shear thickening liquid is extended, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220221A_ABST
    Figure CN119220221A_ABST
Patent Text Reader

Abstract

The invention provides a multiphase shear thickening fluid and a preparation method thereof, and relates to the technical field of shear thickening. The multiphase shear thickening fluid provided by the invention is prepared from the following components in percentage by mass: 92.5 to 99.5 percent of single-phase shear thickening fluid and 0.5 to 7.5 percent of second dispersed phase particles, the second dispersion phase particle is a zeolite imidazate framework ZIF-8; the single-phase shear thickening fluid is prepared from the following components in percentage by mass: 38 to 75 percent of polymer polyol and 25 to 62 percent of spherical silicon dioxide nanoparticles, wherein the mass of the polymer polyol is 100 percent. In the preparation and storage periods of the shear thickening fluid, the dispersion uniformity of the nano particles is high, the nano particles are not easy to settle to be converted into a solid form, the dispersion stability is good, and the shear thickening fluid has better shear thickening performance and plays a positive role in improvement and performance adjustment of the shear thickening fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shear thickening fluids, and in particular to a multiphase shear thickening fluid and a preparation method thereof. Background Art

[0002] Shear Thickening Fluid (STF) is a non-Newtonian fluid composed of dispersed phase particles and dispersion medium, which exhibits non-Newtonian fluid behavior under specific shear conditions. Its viscosity increases with the increase of shear stress or shear rate, and usually this viscosity increase can exceed one order of magnitude. Therefore, shear thickening fluid can automatically adjust its own mechanical properties according to the stimulation of environmental stress field, thus showing good application prospects in the fields of personal protection and impact and vibration reduction.

[0003] Most of the traditional research on shear thickening materials focuses on single dispersed phase systems. The dispersed phase particles used are mainly micro-nano inorganic particles such as calcium carbonate (CaCO3) and silicon dioxide (SiO2) and organic micro-nano particles such as polymethyl methacrylate (PMMA) and polystyrene (PS). The dispersion medium mainly includes polyethylene glycol, ethylene glycol, etc. The shear thickening performance of this system is highly dependent on the dispersed phase and the dispersion medium, among which the dispersed phase particles are the most important influencing factors. The occurrence of shear thickening mainly depends on the hydrogen bonds and friction contact networks between the dispersed phase particles and the dispersion medium, so the shear thickening performance is not easy to adjust. In addition, the solid particles in this system tend to aggregate due to their high density and surface interactions, resulting in sedimentation and loss of shear thickening performance, and the application value is not high. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a new form of multiphase shear thickening fluid and a preparation method thereof. During the preparation and storage of the shear thickening fluid of the present invention, the nanoparticles have high uniformity of dispersion, are not easy to produce sedimentation and transform into a solid form, have good dispersion stability, and have better shear thickening performance, which plays a positive role in the improvement and performance adjustment of the shear thickening fluid.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a multiphase shear thickening fluid, which comprises, by weight percentage, 92.5-99.5% of a single-phase shear thickening liquid and 0.5-7.5% of second dispersed phase particles; the second dispersed phase particles are zeolite imidazolate framework ZIF-8;

[0007] Taking the mass of the single-phase shear thickening liquid as 100%, the single-phase shear thickening liquid comprises 38-75% of polymer polyol and 25-62% of spherical silicon dioxide nanoparticles.

[0008] Preferably, the polymer polyol comprises polyethylene glycol and / or polypropylene glycol.

[0009] Preferably, the molecular weight of the polyethylene glycol is 400-600 g / mol, and the molecular weight of the polypropylene glycol is 400-1000 g / mol.

[0010] Preferably, the particle size of the spherical silica nanoparticles is 20 to 500 nm.

[0011] Preferably, the preparation method of the zeolite imidazolate framework ZIF-8 comprises the following steps:

[0012] Dissolve zinc acetate in methanol to obtain solution A;

[0013] Dissolve 2-methylimidazole in methanol to obtain solution B;

[0014] The solution A is mixed with the solution B to form an insoluble substance, and the zeolite imidazolate framework ZIF-8 is obtained through crystal growth and solid-liquid separation.

[0015] Preferably, the mass ratio of zinc acetate in solution A to 2-methylimidazole in solution B is 1:(2-3.1).

[0016] Preferably, the crystal growing temperature is 15-25° C. and the growing time is 9-12 hours.

[0017] The present invention provides a method for preparing the multiphase shear thickening fluid described in the above scheme, comprising the following steps:

[0018] first dispersing spherical silica nanoparticles into a polymer polyol to obtain a single-phase shear thickening fluid;

[0019] The second dispersed phase particles are dispersed in the single-phase shear thickening liquid to obtain the multiphase shear thickening fluid.

[0020] Preferably, the first dispersing comprises: intermittently adding spherical silica nanoparticles to the polymer polyol in batches under mechanical stirring.

[0021] Preferably, the second dispersion is ultrasonic dispersion.

[0022] The present invention provides a multiphase shear thickening fluid, which comprises 92.5-99.5% of a single-phase shear thickening fluid and 0.5-7.5% of a second dispersed phase particle, in terms of mass percentage; the second dispersed phase particle is a zeolite imidazolate framework ZIF-8; based on the mass of the single-phase shear thickening fluid being 100%, the single-phase shear thickening fluid comprises 38-75% of a polymer polyol and 25-62% of spherical silica nanoparticles. The present invention introduces polyhedral second dispersed phase particles (i.e., zeolite imidazolate framework ZIF-8) into the single-phase shear thickening fluid, and the interaction between particles in the shear thickening fluid increases the point-to-face and face-to-face contact between particles in addition to the point-to-point contact of spherical SiO2. In addition, the second dispersed phase particles can effectively enhance the friction contact between dispersed phase particles. Therefore, under shearing action, the relative sliding and rotation of the second dispersed phase particles caused by the polyhedral morphology are worse than those of spherical SiO2 particles, and the rough surface also enhances the friction between particles. This not only enhances the shear thickening performance, but also improves the dispersion stability of the shear thickening system.

[0023] The present invention provides a method for preparing the multiphase shear thickening fluid described in the above scheme. The preparation method provided by the present invention is simple to operate and has mild conditions. The new shear thickening system has outstanding shear thickening performance and plays a positive role in the improvement and performance adjustment of the shear thickening fluid. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD pattern of the second dispersed phase particles synthesized in Example 1 of the present invention;

[0025] Figure 2 This is a SEM image of the second dispersed phase particles synthesized in Example 1 of the present invention;

[0026] Figure 3 This is the TGA curve of the second dispersed phase particles synthesized in Example 1 of the present invention;

[0027] Figure 4 The steady-state rheological curve of the single-phase shear thickening fluid prepared in Example 1 of the present invention;

[0028] Figure 5 is the steady-state rheological curve of the multiphase shear thickening fluid described in Examples 1 to 4 of the present invention;

[0029] Figure 6 is the steady-state rheological curve of the multiphase shear thickening fluid described in Examples 5 and 6 of the present invention;

[0030] Figure 7 This is a comparison photograph of the dispersion stability of the single-phase shear thickening fluid and the multiphase shear thickening fluid samples in Example 1 of the present invention after standing for two months. DETAILED DESCRIPTION

[0031] The invention provides a multiphase shear thickening fluid, which comprises, by weight percentage, 92.5-99.5% of a single-phase shear thickening liquid and 0.5-7.5% of second dispersed phase particles; the second dispersed phase particles are zeolite imidazolate framework ZIF-8.

[0032] The second dispersed phase particles, namely, zeolite imidazolate framework ZIF-8, are first described below.

[0033] In the present invention, the zeolite imidazolate framework ZIF-8 has a structure shown in Formula I.

[0034]

[0035] In the present invention, the zeolite imidazolate framework ZIF-8 is preferably obtained by self-production, and the preparation method of the zeolite imidazolate framework ZIF-8 preferably comprises the following steps:

[0036] Dissolve zinc acetate in methanol to obtain solution A;

[0037] Dissolve 2-methylimidazole in methanol to obtain solution B;

[0038] The solution A is mixed with the solution B to form an insoluble substance, and the zeolite imidazolate framework ZIF-8 is obtained through crystal growth and solid-liquid separation.

[0039] In the present invention, the zinc acetate is preferably zinc acetate dihydrate; the concentration of zinc acetate in the solution A is preferably 0.04-0.09 g / mL; the concentration of 2-methylimidazole in the solution B is preferably 0.12-0.15 g / mL. The present invention has no special requirements for each dissolution process, and it is sufficient to completely dissolve zinc acetate or 2-methylimidazole, such as dissolving under ultrasonic conditions or stirring conditions.

[0040] In the present invention, the mass ratio of zinc acetate in solution A to 2-methylimidazole in solution B is preferably 1:(2-3.1), more preferably 1:(2.2-2.5). In the present invention, the mixing of solution A and solution B is preferably: quickly pouring solution A into solution B, and then ultrasonicating for 10 minutes.

[0041] After solution A and solution B are mixed, the mixed solution gradually becomes turbid and generates a large amount of white solid insoluble matter. Then, the present invention performs crystal growth and solid-liquid separation to obtain the zeolite imidazolate framework ZIF-8.

[0042] In the present invention, the crystal growing is preferably carried out under static conditions; the temperature of the crystal growing is preferably 15 to 25° C., and the time is preferably 9 to 12 hours.

[0043] The present invention has no special requirements for the solid-liquid separation method, and any solid-liquid separation method known in the art can be used, such as centrifugation. After the solid-liquid separation is completed, the present invention preferably washes the obtained solid with methanol.

[0044] In the present invention, since the zeolite imidazolate framework ZIF-8 is hygroscopic, before use, the present invention preferably performs vacuum activation on the zeolite imidazolate framework ZIF-8.

[0045] In the present invention, the temperature of the vacuum activation is preferably 100° C., and the time is preferably 12 hours. The vacuum degree of the vacuum activation is not particularly limited in the present invention, and any vacuum degree known in the art may be used. The present invention effectively removes moisture from the second phase particles through vacuum activation, improves the purity and stability of the material, and obtains high-quality second phase materials.

[0046] In the present invention, the zeolite imidazolate framework ZIF-8 is a typical rhombic dodecahedron structure.

[0047] The multiphase shear thickening fluid is described below.

[0048] In the present invention, the mass content of the second dispersed phase particles in the multiphase shear thickening fluid is preferably 0.5-7.5%, specifically 0.5%, 1%, 1.5%, 2%, 3%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or 7.5%, which are not enumerated here; the remainder is a single-phase shear thickening liquid.

[0049] In the present invention, based on the mass of the single-phase shear thickening fluid being 100%, the single-phase shear thickening fluid comprises 38-75% of polymer polyol and 25-62% of spherical silica nanoparticles; preferably, the content of the polymer polyol is 40-70%, more preferably 50-60%, most preferably 55%; the remainder is spherical silica nanoparticles.

[0050] In the present invention, the polymer polyol preferably includes polyethylene glycol (PEG) and / or polypropylene glycol (PPG); the molecular weight of the polyethylene glycol is preferably 400-600 g / mol, and the molecular weight of the polypropylene glycol is preferably 400-1000 g / mol. In a specific embodiment, the molecular weight of the polyethylene glycol used is 400 g / mol.

[0051] In the present invention, the particle size of the spherical silica nanoparticles is preferably 20 to 500 nm, specifically 20 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, which are not listed here in detail.

[0052] The present invention introduces polyhedral second dispersed phase particles (i.e., zeolite imidazolate framework ZIF-8) into a single-phase shear thickening liquid. In addition to the point-to-point contact of spherical SiO2, the interaction between particles in the shear thickening liquid increases the point-to-face and face-to-face contact between particles. In addition, the second dispersed phase particles can effectively enhance the frictional contact between dispersed phase particles. Therefore, under shearing, the relative sliding and rotation of the second dispersed phase particles caused by the polyhedral morphology are worse than those of spherical SiO2 particles, and the rough surface also enhances the friction between particles. This not only enhances the shear thickening performance, but also enhances the dispersion stability of the shear thickening system.

[0053] The present invention provides a method for preparing the multiphase shear thickening fluid described in the above scheme, comprising the following steps:

[0054] first dispersing spherical silica nanoparticles into a polymer polyol to obtain a single-phase shear thickening fluid;

[0055] The second dispersed phase particles are dispersed in the single-phase shear thickening liquid to obtain the multiphase shear thickening fluid.

[0056] The invention first disperses spherical silicon dioxide nanoparticles into polymer polyol to obtain a single-phase shear thickening liquid.

[0057] Before the first dispersion, the present invention preferably first vacuum-dries the spherical silica nanoparticles. In the present invention, the vacuum drying temperature is preferably 120° C. and the time is preferably 12 hours.

[0058] In the present invention, the first dispersion preferably includes: adding spherical silica nanoparticles to the polymer polyol in batches and intermittently under mechanical stirring. In the present invention, the mechanical stirring rate is preferably 400-1300 rpm. After all the spherical silica nanoparticles are added to the polymer polyol and stirred evenly, the present invention preferably allows the mixture to stand for 6-10 hours to eliminate bubbles generated by stirring, thereby obtaining a single-phase shear thickening liquid.

[0059] After obtaining the single-phase shear thickening liquid, the present invention disperses the second dispersed phase particles into the single-phase shear thickening liquid to obtain the multiphase shear thickening fluid.

[0060] In the present invention, the second dispersion is preferably ultrasonic dispersion; the ultrasonic dispersion time is preferably 2 to 4 hours. After the second dispersion is completed, the present invention preferably places the obtained dispersion system in a vacuum drying oven at 80° C. for 12 hours until a small amount of bubbles and water that may be mixed in are completely removed, and then sealed for storage to obtain the multiphase shear thickening fluid.

[0061] There are many preparation methods for traditional STF, mainly including mechanical mixing, ultrasonic oscillation and ball milling. The earliest preparation method of STF was mechanical stirring. This method has certain defects. There are many bubbles in the prepared shear thickening fluid, which affects the results of the final rheological test. As the research continued, the researchers found that ultrasonic oscillation can effectively avoid the generation of bubbles, but at the same time, the dispersed phase cannot be mixed evenly when the concentration is too high. Because the ball milling method can prevent the powder from flying very well, many teams use the ball milling mixing method to prepare shear thickening fluid. However, the ball milling time varies, there is a certain controversy, and the preparation cycle exceeds 24 hours. In addition, this method is prone to produce grinding chips and introduce impurities. The use of mechanical stirring (first dispersion) combined with ultrasound (second dispersion) in the present invention can make the dispersion medium and the dispersed phase better mixed and greatly reduce the operation time.

[0062] The multiphase shear thickening fluid and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0063] The characterization methods used in the following examples are as follows:

[0064] Structural Characterization of Second Dispersed Phase Particles

[0065] The crystal form of the second dispersed phase particles was characterized by X-ray powder diffractometer (XRD, Bruker D8 Advance). Tube type: Cu target, ceramic X-ray tube; tube power: 2.2 kW, ultrafast Links array detector linear range: >7.6×10 6 cps, background: <0.1cps, scanning mode: vertical θ / θ goniometer, the goniometer is placed vertically, detector: energy dispersive two-dimensional array detector, tube voltage: 40KV, tube current: 40mA, 2θ scanning range: 5~50°, step length: 0.02°, scanning speed: 5° / min, solid sample powder particle size: 200~300 mesh.

[0066] It should be noted that the second dispersed phase particles of the present invention include not only crystals whose peak diffraction angles in X-ray powder diffraction are completely consistent or ±0.2°, but also crystals whose diffraction angles are consistent within an error of ±0.2°.

[0067] The characteristic peak refers to a diffraction peak with relatively high peak intensity in the X-ray powder diffraction spectrum, for example, a relative peak intensity higher than 10%.

[0068] The microstructure of the second dispersed phase particles was characterized by a Zeiss field emission scanning electron microscope (GeminiSEM 360, Zeiss, Germany) under the following operating conditions: working distance (WD) of 6.6 mm and electron acceleration voltage (EHT) of 5.0 kV.

[0069] The mass of ZIF-8 material was measured with a thermal analyzer (STA449F3, NATZSCH, Germany) to analyze the thermal stability of the second dispersed phase particles. The temperature was increased from 40 to 900 °C at a rate of 10 °C / min in a N2 atmosphere with a flow rate of 50 mL / min.

[0070] Steady-state shear thickening performance test: The steady-state rheological properties of the prepared single-phase and multiphase shear thickening fluids were tested by a rotational rheometer (Anton-paar MCR302), using a PP25 / TG plate system, and the measurement temperature was maintained at 25°C by an automatic temperature control device. During the measurement, the gap between the plates was maintained at 1 mm, and the shear rate range of the steady-state rheological test was 0.01 to 1000 S -1 .

[0071] Stability test of shear thickening fluid: After placing the single-phase and multiphase shear thickening fluid samples prepared differently at room temperature for 60 days, their solid-liquid separation phenomenon was observed.

[0072] Example 1

[0073] (1) Synthesis of Second Dispersed Phase Particles

[0074] 9.4 g of zinc acetate dihydrate was dissolved in 150 mL of methanol, and ultrasonicated until completely dissolved to obtain solution A. Then 21.6 g of 2-methylimidazole was dissolved in 150 mL of methanol to obtain a transparent solution B. Solution A was quickly poured into solution B and ultrasonicated for 10 min. The mixed solution gradually became turbid and a large amount of white solid insoluble matter was generated. The obtained mixture was allowed to stand at room temperature overnight, centrifuged, washed with methanol, and finally activated at 100 ° C under vacuum for 12 h to obtain white powder particles, i.e., the second dispersed phase particles.

[0075] The XRD spectrum of the synthesized second dispersed phase particles is shown in Figure 1 As shown. Figure 1 It can be seen that within the 2θ scanning range of 5 to 50°, the synthesized second dispersed phase particles have significantly different characteristic diffraction peaks, belonging to a crystalline product. At the same time, the characteristic peaks of the sample are relatively sharp, indicating that the synthesized second dispersed phase particles have a high degree of crystallinity and no other impurities.

[0076] Figure 2 This is a SEM image of the synthesized second dispersed phase particles. From the morphology image, it can be seen that the synthesized second dispersed phase material has a typical rhombic dodecahedron structure and has good monodispersity.

[0077] The thermal stability of the synthesized second dispersed phase particles was further investigated using TGA. Figure 3As shown. According to the TGA curve, it can be seen that the sample has no obvious mass loss in the range of 430℃, and a slight weight loss phenomenon begins to appear at 510℃. As the temperature rises, the sample structure is decomposed, and the weight loss is about 51.3% in the range of 600-870℃. According to the TGA analysis results, it shows that the synthesized material structure has good thermal stability, laying the foundation for the further development of shear thickening fluid.

[0078] (2) Preparation of multiphase shear thickening fluid

[0079] First, SiO2 particles with an average particle size of 500nm were vacuum dried at 120℃ for 12h, and the dispersed phase and dispersion medium were weighed according to the mass ratio, and the mass fraction of the dispersed phase was 55%; at room temperature, the SiO2 particles were slowly added to PEG in batches with mechanical stirring at 400rpm, stirred until uniform, and allowed to stand for 8h to obtain a single-phase shear thickening liquid, and then the second dispersed phase particles were stirred and dispersed in the single-phase shear thickening liquid according to the mass fraction, and the second dispersed phase particle content was 1.5wt%; the obtained mixed solution was ultrasonically treated for 3h, placed in a vacuum drying oven at 80℃ for 12h, until a small amount of bubbles and moisture that may be mixed in were completely removed, and then sealed and stored to obtain a multiphase shear thickening fluid.

[0080] The steady-state rheological characterization results of the prepared single-phase shear thickening fluid are as follows: Figure 4 As shown. Figure 4 It can be seen that the single-phase shear thickening fluid follows the shear thickening behavior of "thinning-thickening-thinning", but the peak viscosity after shear thickening is lower.

[0081] The steady-state rheological characterization results of the prepared multiphase shear thickening fluid are shown in Figure 5 As shown. Figure 5 It can be found that at the same shear rate, the shear stress increases with the increase of shear rate. The steady-state rheological test results of multiphase STF also show that the introduction of the second dispersed phase leads to significant changes in viscosity and critical shear rate. The addition of a second dispersed phase can change the interaction force between the particles of the STF dispersed phase, affecting the shear thickening effect, thereby achieving the regulation of the rheological behavior of the shear thickening fluid.

[0082] Traditional shear thickening fluids face the problem of weakening their shear thickening properties due to the sedimentation of dispersed phase particles in the dispersion medium. Therefore, the dispersibility and stability of the prepared samples were studied. Figure 7 As shown, Figure 7 In the figure, (a) is a single-phase shear thickening fluid, and (b) is a multiphase shear thickening fluid. After standing for 60 days, the multiphase shear thickening fluid showed the best stability, while the single-phase shear thickening fluid showed obvious stratification characteristics. It can be seen that the multiphase shear thickening fluid of the present invention has good stability.

[0083] Example 2

[0084] (1) Synthesis of Second Dispersed Phase Particles

[0085] Same as Example 1.

[0086] (2) Preparation of multiphase shear thickening fluid

[0087] SiO2 particles with an average particle size of 500 nm were vacuum dried at 120°C for 12 hours, and the dispersed phase and the dispersion medium were weighed according to the mass ratio, and the mass fraction of the dispersed phase was 55%; at room temperature, the SiO2 particles were slowly added to the PEG in batches at 600 rpm mechanical stirring, stirred until uniform, and allowed to stand for 8 hours to obtain a single-phase shear thickening liquid. The second dispersed phase particles were stirred and dispersed in the single-phase shear thickening liquid according to the mass fraction, and the second dispersed phase particle content was 3.0wt%. The resulting mixed solution was ultrasonically treated for 3 hours, placed in a vacuum drying oven and dried at 80°C for 12 hours until a small amount of bubbles and moisture that may have been mixed in were completely removed, and then sealed for storage. The steady-state rheological characterization results of the prepared multiphase shear thickening fluid are shown in Figure 2. Figure 5 shown.

[0088] Example 3

[0089] (1) Synthesis of Second Dispersed Phase Particles

[0090] Same as Example 1.

[0091] (2) Preparation of multiphase shear thickening fluid

[0092] First, SiO2 particles with an average particle size of 500nm were vacuum dried at 120℃ for 12h, and the dispersed phase and the dispersion medium were weighed according to the mass ratio, and the mass fraction of the dispersed phase was 55%; at room temperature, the SiO2 particles were slowly added to the PEG in batches with mechanical stirring at 600rpm, stirred until uniform, and allowed to stand for 8h to obtain a single-phase shear thickening liquid. The second dispersed phase particles were stirred and dispersed in the single-phase shear thickening liquid according to the mass fraction, and the second dispersed phase particle content was 4.5wt%. The resulting mixed solution was ultrasonically treated for 3h, placed in a vacuum drying oven and dried at 80℃ for 12h until a small amount of bubbles and moisture that may have been mixed in were completely removed, and then sealed for storage. The steady-state rheological characterization results of the prepared multiphase shear thickening fluid are shown in Figure 2. Figure 5 shown.

[0093] Example 4

[0094] (1) Synthesis of Second Dispersed Phase Particles

[0095] Same as Example 1.

[0096] (2) Preparation of multiphase shear thickening fluid

[0097] First, SiO2 particles with an average particle size of 500nm were vacuum dried at 120℃ for 12h, and the dispersed phase and the dispersion medium were weighed according to the mass ratio, and the mass fraction of the dispersed phase was 55%; at room temperature, the SiO2 particles were slowly added to the PEG in batches with mechanical stirring at 600rpm, stirred until uniform, and allowed to stand for 8h to obtain a single-phase shear thickening liquid. The second dispersed phase particles were stirred and dispersed in the single-phase shear thickening liquid according to the mass fraction, and the second dispersed phase particle content was 6.0wt%. The resulting mixed solution was ultrasonically treated for 3h, placed in a vacuum drying oven and dried at 80℃ for 12h until a small amount of bubbles and moisture that may have been mixed in were completely removed, and then sealed for storage. The steady-state rheological characterization results of the prepared multiphase shear thickening fluid are shown in Figure 2. Figure 5 shown.

[0098] Example 5

[0099] (1) Synthesis of Second Dispersed Phase Particles

[0100] Same as Example 1.

[0101] (2) Preparation of multiphase shear thickening fluid

[0102] First, SiO2 particles with an average particle size of 20 nm were vacuum dried at 120°C for 12 hours, and the dispersed phase and the dispersion medium were weighed according to the mass ratio, and the mass fraction of the dispersed phase was 25%; at room temperature, the SiO2 particles were slowly added to the PEG in batches with mechanical stirring at 600 rpm, stirred until uniform, and allowed to stand for 8 hours to obtain a single-phase shear thickening liquid. The second dispersed phase particles were stirred and dispersed in the single-phase shear thickening liquid according to the mass fraction, and the second dispersed phase particle content was 0.5wt%. The resulting mixed solution was ultrasonically treated for 3 hours, placed in a vacuum drying oven and dried at 80°C for 12 hours until a small amount of bubbles and moisture that may have been mixed in were completely removed, and then sealed for storage. The steady-state rheological characterization results of the prepared multiphase shear thickening fluid are shown in Figure 2. Figure 6 shown.

[0103] Example 6

[0104] (1) Synthesis of Second Dispersed Phase Particles

[0105] Same as Example 1.

[0106] (2) Preparation of multiphase shear thickening fluid

[0107] First, SiO2 particles with an average particle size of 20 nm were vacuum dried at 120°C for 12 hours, and the dispersed phase and the dispersion medium were weighed according to the mass ratio, and the mass fraction of the dispersed phase was 25%; at room temperature, the SiO2 particles were slowly added to the PEG in batches with mechanical stirring at 600 rpm, stirred until uniform, and allowed to stand for 8 hours to obtain a single-phase shear thickening liquid. The second dispersed phase particles were stirred and dispersed in the single-phase shear thickening liquid according to the mass fraction, and the second dispersed phase particle content was 1.0wt%. The resulting mixed solution was ultrasonically treated for 3 hours, placed in a vacuum drying oven and dried at 80°C for 12 hours until a small amount of bubbles and moisture that may have been mixed in were completely removed, and then sealed for storage. The steady-state rheological characterization results of the prepared multiphase shear thickening fluid are shown in Figure 2. Figure 6 shown.

[0108] Depend on Figure 6 It can be seen that the dispersed phase particle size has a significant effect on the thickening performance of the shear thickening fluid. Compared with the shear thickening fluid prepared with 500nm SiO2, the critical shear thickening rate of the multiphase shear thickening fluid obtained with SiO2 particles with an average particle size of 20nm is significantly reduced, indicating that its shear thickening effect is easier to trigger.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A multiphase shear thickening fluid, characterized in that: In terms of mass percentage, it comprises 92.5-99.5% of a single-phase shear thickening liquid and 0.5-7.5% of second dispersed phase particles; the second dispersed phase particles are zeolite imidazolate framework ZIF-8; Taking the mass of the single-phase shear thickening liquid as 100%, the single-phase shear thickening liquid comprises 38-75% of polymer polyol and 25-62% of spherical silicon dioxide nanoparticles.

2. The multiphase shear thickening fluid according to claim 1, characterized in that: The polymer polyol includes polyethylene glycol and / or polypropylene glycol.

3. The multiphase shear thickening fluid according to claim 2, characterized in that: The molecular weight of the polyethylene glycol is 400-600 g / mol, and the molecular weight of the polypropylene glycol is 400-1000 g / mol.

4. The multiphase shear thickening fluid according to claim 1, characterized in that: The particle size of the spherical silicon dioxide nanoparticles is 20 to 500 nm.

5. The multiphase shear thickening fluid according to claim 1, characterized in that: The preparation method of the zeolite imidazolate framework ZIF-8 comprises the following steps: Dissolve zinc acetate in methanol to obtain solution A; Dissolve 2-methylimidazole in methanol to obtain solution B; The solution A is mixed with the solution B to form an insoluble substance, and the zeolite imidazolate framework ZIF-8 is obtained through crystal growth and solid-liquid separation.

6. The phase shear thickening fluid according to claim 5, characterized in that: The mass ratio of zinc acetate in the solution A to 2-methylimidazole in the solution B is 1:(2-3.1).

7. The phase shear thickening fluid according to claim 5 or 6, characterized in that: The crystal growing process is performed at a temperature of 15 to 25° C. for 9 to 12 hours.

8. The method for preparing a multiphase shear thickening fluid according to any one of claims 1 to 7, characterized in that: The following steps are involved: first dispersing spherical silica nanoparticles into a polymer polyol to obtain a single-phase shear thickening fluid; The second dispersed phase particles are dispersed in the single-phase shear thickening liquid to obtain the multiphase shear thickening fluid.

9. The preparation method according to claim 8, characterized in that: The first dispersion comprises: intermittently adding spherical silica nanoparticles to the polymer polyol in batches under mechanical stirring.

10. The preparation method according to claim 8, characterized in that: The second dispersion is ultrasonic dispersion.